Evaluación del servicio de atención al usuario en el área de Dirección de Tránsito del Gobierno Autónomo Descentralizado Municipal de Tosagua - Chávez Briones, Karen Alejandra (2021)
This research work was carried out in order to evaluate the user service of the Transit Directorate of the Autonomous Decentralized Municipal Government of the Tosagua canton to improve the quality of the service. The methodology that was used was field and documentary; Through an interview with the director of the transit area, it was possible to know the current situation of the services offered on a daily basis. Subsequently, a survey of dimensions of the SERVQUAL model was applied, to detect the main shortcomings of the service offered in said area, then a SWOT was carried out based on the results obtained from the survey of the area under study, such as; lack of air conditioning, delay in the automated system on duty, little training for public servants, and the lack of space to carry out the respective payments of procedures. Finally, it is necessary to implement an improvement plan that helps to optimize these weaknesses that directly affect the user.